2018
DOI: 10.1097/mao.0000000000001652
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes With a Slim, Modiolar Cochlear Implant Electrode Array

Abstract: CI532 array insertion results in consistent scala tympani location and provides expected audiologic performance. Initial hearing preservation results are not consistent with current electro-acoustic arrays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 20 publications
6
73
0
1
Order By: Relevance
“…Due its reduced size, it can be inserted through the round window, which has been shown to be beneficial for ensuring initial scala tympani placement and results in better hearing preservation and improved speech perception scores [2,10,20]. Previously reported gains in postoperative speech perception and quality of life measures with the Nucleus CI532 are in line with those reported for other devices and are potentially better than with earlier Cochlear devices [3,10,23].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Due its reduced size, it can be inserted through the round window, which has been shown to be beneficial for ensuring initial scala tympani placement and results in better hearing preservation and improved speech perception scores [2,10,20]. Previously reported gains in postoperative speech perception and quality of life measures with the Nucleus CI532 are in line with those reported for other devices and are potentially better than with earlier Cochlear devices [3,10,23].…”
Section: Introductionmentioning
confidence: 72%
“…Previous studies using the Slim Modiolar electrode array showed consistent perimodiolar placement and scala tympani insertions in at least 87% of the patients assessed with imaging [1][2][3]. They reported hearing preservation is better than with older perimodiolar and straight designs, but possibly not as good as hybrid or electroacoustic devices that are specifically designed for hearing preservation [2,3,[9][10][11].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It was observed that independent of the type of electrode used, full scala tympani (ST) position [8] and preservation of residual hearing [8,10] is more likely using a RW or eRW approach, compared to the CS approach. These findings might contribute to the fact that to-date, eRW and RW approaches were used in 91.8% (236/257) of the participants in the five studies that investigated the SPE [11,12,[14][15][16].…”
Section: Rationalementioning
confidence: 99%